Strategies used in Arabic-English translation of idiomatic expressions in the novel men in the sun - Zayed, Mujahed Hossien Tahir; Husain, Salina; Wan Sulong, Wan Muhammad; Yahya, Yasir (Review of International Geographical Education Online, 2021)
The current study aims to investigate the strategies employed by the Translator Hilary Kilpatrick in translating the idiomatic expressions in the novel Men in the Sun by Ghassan Kanafani from Arabic into English. The researcher adopts mixed-methods approach to achieve the objectives of the study. Thus, this study adopts Baker's (2018) and Newmark's (1988) models to identify the strategies of translating idioms in this novel. Additionally, a quantitative analysis is carried out to calculate the frequencies of each translation strategy. Then, the translations along with the strategies were presented to a professional translator and a translation lecturer to determine the appropriate strategies that convey the meaning of the Arabic idioms into English. The results of the study reveal that the translator mostly used the strategy of paraphrasing in translating the idioms followed by literal translation. The strategy of translating an idiom with a TL idiom which is similar in form but different in meaning came in third place and the strategy of translating an idiom by a TL idiom which is similar in form and meaning was the least employed strategy in translating the idioms of this novel. The strategies of paraphrasing and translating an idiom by an idiom which is similar in form and meaning were determined as the most appropriate strategies to render Arabic idioms into English.